2002
DOI: 10.1002/jmri.10156
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution selective three‐dimensional magnetic resonance coronary angiography with navigator‐echo technique: Segment‐by‐segment evaluation of coronary artery stenosis

Abstract: Purpose:To investigate the feasibility of high-resolution selective three-dimensional (3D) magnetic resonance coronary angiography (MRCA) in the evaluation of coronary artery stenoses. Materials and Methods:In 12 patients with coronary artery stenoses, MRCA of the coronary artery groups, including the coronary segments with stenoses of 50% or greater based on conventional x-ray coronary angiography (CAG), was performed with double-oblique imaging planes by orienting the 3D slab along the major axis of each rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
4
10
0
1
Order By: Relevance
“…In this study, the absent segments on target-volume MRCA (91 of 638 segments) mainly comprised the distal segments of the coronary arteries: the distal LAD artery (28 segments, 30.8%), the PDA (27 segments, 30%), and the distal LCx artery (25 segments, 27.5%). This observation is comparable with results from previous studies using target volume MRCA (26,27). The per-patient analysis, after excluding the absent segments in group B, also showed that coronary artery assessibility was comparable between CTCA and MRCA.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the absent segments on target-volume MRCA (91 of 638 segments) mainly comprised the distal segments of the coronary arteries: the distal LAD artery (28 segments, 30.8%), the PDA (27 segments, 30%), and the distal LCx artery (25 segments, 27.5%). This observation is comparable with results from previous studies using target volume MRCA (26,27). The per-patient analysis, after excluding the absent segments in group B, also showed that coronary artery assessibility was comparable between CTCA and MRCA.…”
Section: Discussionsupporting
confidence: 92%
“…3D acquisition techniques, which acquire some amount of volume data in a single acquisition, were soon developed, and data acquisition with 3D sequences is now the mainstream in coronary MRA. [5][6][7][8][9][10][11][12][13] In 3D acquisition, data is acquired over a wide range at one time, and respiratory gating, such as the navigator echo technique, is therefore used to directly monitor the position of the diaphragm. 6 Respiratory gating enables MRA with high spatial resolution while the patient breathes quietly.…”
Section: Coronary Mramentioning
confidence: 99%
“…Results reported for coronary MRA have varied widely, with sensitivity values ranging from 40z to 90z as compared to those for CAG. [2][3][4][5]10,11 It is thought that this variation can be attributed to the diŠerent MRI systems and acquisition sequences employed as well as to diŠerences in the target segments of the coronary arteries. A multicenter study using MRI systems of the same model and the same acquisition technique (3D-segmented k-space gradient-echo sequence with respiratory gating employing the navigator echo technique) has recently been conducted.…”
Section: Diagnostic Capabilities Of Coronary Mramentioning
confidence: 99%
“…In contrast to non-invasive imaging of the coronary vessels as computed tomography (CT) (e.g., [1,2]) or magnetic resonance imaging (e.g., [3,4]), X-ray imaging generates projections in real-time. The working views are traditionally operator selected in order to subjectively minimize vessel overlap and foreshortening [5,6].…”
Section: Introductionmentioning
confidence: 99%